PENGARUH NON PERFORMING LOAN, LOAN TO DEPOSIT RATIO DAN DANA PIHAK KETIGA TERHADAP PROFITABILITAS PADA PERUSAHAAN PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2015 - 2019 - FERAWATI . (JURNAL ILMIAH KOHESI, 2020)
The purpose of this study is to analyze the influence of Non Performing Loans, Loan to Deposit Ratios and Third Party Fundson profitability in banking companies listed on the Indonesia Stock Exchange for the period 2015-2019. The population in thisstudy was 43 banking companies listed on the Indonesia Stock Exchange for the period 2015-2019. A sample of 24 bankingcompanies listed on the Indonesia Stock Exchange for the period 2015-2019. The research methodology used is multiplelinear regression analysis. The results prove that Non Performing Loan has an effect on profitability in banking companieslisted on the Indonesia Stock Exchange period 2015-2019. Loan to Deposit Ratio has no effect on profitability in bankingcompanies listed on the Indonesia Stock Exchange for the period 2015-2019. Third Party Funds affect profitability of bankingcompanies listed on the Indonesia Stock Exchange for the period 2015-2019. Non Performing Loans, Loan to Deposit Ratiosand Third Party Funds affect profitability in banking companies listed on the Indonesia Stock Exchange for the period 2015-2019 with adjusted R Square (R2) coefficient of determination of 0.028 or equal to 2.8% while the remaining 92.8% isinfluenced by other unexamined variables such as capital adequacy, growth in customer numbers and BOPO.